PENGEMBANGAN ENSIKLOPEDIA BUMI DAN ANTARIKSA SERTA KAITANNYA DENGAN AL QURAN PENDIDIKAN FISIKA UNTUK MAHASISWA - Putra, Adi Nugraha; Maison, Maison; Susanti, Nova (EduFisika: Jurnal Pendidikan Fisika, 2019)
Research aims to develop the encyclopedia and know the student's perception of the Encyclopedia of Earth and Space. The encyclopedia development uses the development of ADDIE models. Subjects of this study were material experts, media experts and physics education students as much as 39 students. Research instruments used validation sheets and quisionare. Data analysis techniques for product eligibility validity are calculated using formula Aiken. The encyclopedia contains three material chapters: Earth structure, Solar System, asteroid and comet. The material is associated with relevant Quranic verses. Expert validation results are obtained by product eligibility scores of 0.8 with high enough categories. Student perception test results gained a percentage of 84.61% good.